Harnessing entomopathogenic nematodes for sustainable pest management: mechanisms, challenges, and innovations - Kaur, Amandeep; Sirengo, David Kihoro; Karki, Pratibha; Powers, Thomas O.; Brown, Amanda M. V. (Frontiers in Plant Science, 2026)
Entomopathogenic nematodes (EPNs) of the genera Heterorhabditis and Steinernema are increasingly recognized as potent biological control agents due to their ability to infect and kill diverse insect pest taxa through a symbiotic partnership with insect-pathogenic bacteria. Over the last decades, substantial progress has been made in improving EPN field performance through advances in formulation and application methods, use of biodegradable polymers and nanocarriers, and elucidation of stress tolerance mechanisms. However, despite their proven efficacy, large-scale commercialization of EPNs remains limited by high production costs, formulation instability, and environmental constraints. While numerous reviews have separately addressed EPN biology, mass production, or field application independently, a critical and integrative synthesis linking molecular mechanisms, and formulation strategies remains lacking. This review synthesizes current understanding of EPN biology with emphasis on molecular mechanisms governing host localization, invasion, and immune suppression, as well as their biotic ecological interactions within soil environments. We also discuss advances in stress tolerance mechanisms, innovations in formulation, and outline future research priorities needed to develop ecologically resilient EPN-based biocontrol products. As agriculture shifts toward more regenerative and environmentally sustainable systems, a comprehensive understanding of EPN biology, full ecological potential of EPN-bacteria partnerships holds promise not only for effective pest suppression but also for advancing fundamental understanding of host-microbe interactions and ecosystem resilience.